Emerging Technology in Primary Physical Education in Last Decade: A Bibliometric Analysis - agustin, nurhaningtyas (Universitas Nahdatul Ulama Surabaya, 2025)
Physical education has great potential to be integrated with technology during the implementation. This paper reports bibliometric research on emerging technology in primary physical education during 2015- 2024. This study utilizes Dimensions database. We found it consistent last five-years rising in TiP-PE publications; the most document type on Tip-PE was journal articles; Indonesia is the country with highest publication on Tip-PE; and the highest occurrences keyword along with total link strength is the ‘Education’. Moreover, the cited performance articles of the TiP-PE covered to the Quartile 1 on Scopus, which implies it has good reputation and credibility. These insights offer a thorough basis for scholars, teachers, and decision-makers to enhance their grasp of TiP-PE, steering upcoming efforts toward creative and meaningful advancements at the pedagogy-technology combination.